Contextual factors affecting integration of eye health into school health programme in Zanzibar: a qualitative health system research - Ving Fai Chan; Elodie Yard; Eden Mashayo; Damaris Mulewa; Lesley Drake; Fatma Omar (BMC, 2023)
Abstract Background Short-term school eye health programmes supported by external funders have sustainability issues. This study aimed to understand the contextual factors affecting integrating eye health into the school health programme. Methods We elicited responses from 83 respondents, purposefully selected from the Ministry of Health (n = 7), Ministry of Education and Vocational Training (n = 7), hospitals/eye centres (n = 5), master trainers (4) and schools (n = 60) who participated in in-depth interviews. Their responses were analysed and grouped into contextual factors according to the WHO Consolidated Framework for Implementation Research: stakeholders/political, institutional, physical, cultural, delivery system and others. Themes were then generated, and quotations were presented to illustrate the findings. Results The six contextual factors affecting the integration of eye health into the school eye health programme were i) Stakeholders/political (Good ministry coordination, defined departmental roles and resource mobilisation from multiple stakeholders; Good stakeholder synergies and address current gaps); ii) Institutional (Institutional coordination and adequate clinic space; Securing human and financial resources; Strategic advocacy for institutional resources); iii) Physical (Long travel distance to service points); vi) Cultural (low eye health awareness among parents, teachers and children); iv) Delivery system (Practical approach to increase screening coverage using teachers as screeners; Balance teachers' workload, increase screening sensitivity and follow up and; v) Others (Comprehensive training material and effective training delivery; Improved curriculum, teacher selection and supervision and incentives). Conclusion Integrated school eye health delivery is generally well-received by stakeholders in Zanzibar, with the caveat that investment is required to address the six contextual factors identified in the study.